DIVORCE IN DAGESTAN: MOTIVES AND WAYS OF STABILIZATION (statistical analysis) - Alimova, B M (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the most important issues of morality and ethics, misunderstandings and difficulties in family life. The author of the article analyses reasons and conditions leading to the decay of family and marriage and outlines the ways of preventing violation of ethics of love, family and marriage.